1456. Environmental and Nasal Pathogen Surveillance in Seattle Area Homeless Shelters. (15th December 2022) - Franko, Nicholas M; Rogers, Julia H; Chow, Eric J; Huden, Kristen; Link, Amy C; Han, Peter D; Wolf, Caitlin R; Logue, Jennifer; McDonald, Dylan; Shim, Mi-Hyun M; Hughes, James; Shendure, Jay; et al.
Abstract: Background: The need for community surveillance of respiratory viruses in high-risk settings such as homeless shelters has been underscored by the COVID-19 pandemic. Here, we show that sampling high-touch surfaces is a low-cost, minimally intensive means of community respiratory virus surveillance. Methods: Environmental samples were collected weekly from adult and family homeless shelters in King County, WA from November 2019 – April 2020. At times when residents were present, a 10cm 2 area of selected high-touch surfaces were swabbed and bioaerosol samples were collected in high-traffic areas. Surfaces included entrance and restroom doorknobs, counters, and surfaces unique to each shelter. Study staff collected mid-turbinate swabs from shelter resident participants aged > 3 months with symptoms of acute respiratory illness (ARI). All samples were tested by RT-PCR for 27 viruses. From January 1, 2020 onward, samples were also tested for SARS-CoV-2. Results: A total of 788 environmental swabs, 1509 nasal swabs, and 98 bioaerosol samples from 6 adult and 3 family shelters were tested. Adenovirus (109 positive swabs, 13.8% of tested swabs), rhinovirus (107, 13.6%) and human bocavirus (62, 7.9%) were the most frequently detected viruses in surface swabs. Rhinovirus (160, 10.6%), human coronaviruses (79, 5.24%) and influenza B (43, 2.85%) were the most detected in nasal swabs. All viruses detected in nasal swabs were found in surface swabs. Of 9 surfaces, exterior bathroom doorknobs were the physical location with the highest number of pathogens detected. SARS-CoV-2 was first detected in surface swabs on 3/20/20, and in nasal swabs on 3/10/20. Bioaerosol samples detected virus in a low percentage of samples relative to surface and nasal swabs. Table 1 Count and period prevalence of environmental viral detection by shelter type, November 18, 2019 - April 10, 2020. Figure 1 Number of viral pathogens detected from environmental swabs, disaggregated by shelter type. Figure 2 Bar graphs comparing prevalence of respiratory pathogen detection in mid-turbinate nasal swabs and environmental swabs/bioaerosol samples by epidemiologic week, November 18, 2019 - April 30, 2020. Conclusion: Respiratory viruses detected through environmental sampling in homeless shelters were similar to the viruses detected from ARI episodes in study participants. Environmental surface sampling presents a plausible, minimally invasive method of surveillance for both endemic and emerging respiratory pathogens, as evidenced by the detection of SARS-CoV-2 during the early stages of the pandemic. Further research could focus on sampling public locations for broader community surveillance and culturing viruses found on these surfaces. Disclosures: Michael J. Boeckh, MD PhD, Allovir: Advisor/Consultant|Amazon: Grant/Research Support|Ansun Biopharma: Grant/Research Support|EvrysBio: Advisor/Consultant|Gates Ventures: Grant/Research Support|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Grant/Research Support|GlaxoSmithKline: Advisor/Consultant|GlaxoSmithKline: Grant/Research Support|Helocyte: Advisor/Consultant|Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Kyorin Pharmaceuticals: Advisor/Consultant|Merck: Advisor/Consultant|Merck: Grant/Research Support|Moderna: Advisor/Consultant|Moderna: Grant/Research Support|Regeneron: Grant/Research Support|ReViral: Advisor/Consultant|Symbio: Advisor/Consultant|Takeda: Grant/Research Support|Vir Biotechnology: Advisor/Consultant|Vir Biotechnology: Grant/Research Support Janet A. Englund, MD, AstraZeneca: Advisor/Consultant|AstraZeneca: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Meissa Vaccines: Advisor/Consultant|Merck: Grant/Research Support|Pfizer: Grant/Research Support|Sanofi Pasteur: Advisor/Consultant Helen Y. Chu, MD, MPH, Cepheid: Reagents|Ellume: Advisor/Consultant|Gates Ventures: Grant/Research Support|Merck: Advisor/Consultant|Pfizer: Advisor/Consultant.